Enhancing children’s learning of Malay traditional musical Instruments using multimedia elements in Augmented Reality book - Mahmun, Haziq Ashraf; Che Din, Sharkawi (Universiti Teknologi MARA, Perak, 2025)
The decline in awareness and appreciation of Malay traditional musical instruments among younger generations in Malaysia presents a pressing cultural concern. Due to limited exposure and a lack of engaging educational resources, many children are unfamiliar with instruments like the gambus, rebana, and marwas. This study aims to investigate how multimedia elements in Augmented Reality (AR) books can enhance children’s learning and appreciation of Malay traditional musical instruments. Using a qualitative content analysis approach, six selected AR books were examined to identify the use and effectiveness of multimedia elements such as text, image, video, audio, and animation. These elements were analysed based on their contribution to enhancing engagement, motivation, and knowledge retention. The findings revealed that while video was not utilized in any of the selected AR books, all incorporated text, images, and sound effects, with varying degrees of narration and music. A strong emphasis was placed on interactive 3D and animated features, which significantly enriched user experience and learning outcomes. The results support the application of Mayer’s Multimedia Learning Theory, demonstrating that the combination of visual, auditory, and interactive elements in AR books effectively facilitates children’s understanding and enjoyment of traditional content. This study suggests that AR technology offers a promising tool for cultural preservation and recommends further exploration into its integration within formal education systems.